Oral health status of a sample of disabled population in Iran - Zahrakhanom Hashemi DDS; Abolghasem Hajizamani DMD, PhD; Elham Bozorgmehr DDS; Fereshteh Omrani DDS (Journal of Oral Health and Oral Epidemiology, 2012)
BACKGROUND: A wide range of oral health conditions has been studies in disabled populations. Many studies showedthat the oral health of individuals who were disabled was poor and their oral treatment needs were greater than those ofthe general population. This study aimed to determine caries experience, levels of oral hygiene, periodontal health andprevalence of malocclusion in a sample of disabled subjects.METHODS: Five special care needs schools were randomly selected from the list of schools in Kerman and all attendantswere examined for dental status on the basis of WHO criteria, gingival health and oral hygiene behaviors. Data wereanalyzed by ANOVA and chi-square tests.RESULTS: There were 297 participants in the study. The most frequent group of disability was mental retard. The meandecayed, missing and filled teeth (DMFT) score was 5.14. Ninety percent of subjects had gingival inflammation. Therewas no significant (P = 0.34) difference between caries experiences of different disable groups.CONCLUSIONS: Oral hygiene of disabled groups was poor and their caries experience rate was very high. Special oralhealth care program for them is recommended